Pengaruh Pelatihan Gada Madya Terhadap Work Role Performance Pada Supervisor Keamanan PT. Swabina Gatra - Mi'Rojiah, Barkatul; Amelasasih, Prianggi (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
A staff who will be promoted as a security supervisor needs to receive Gada Madya training to support their competence in carrying out their main duties, one of which is the performance of their work role as a security supervisor. So this research aims to determine the value of work role performance in security supervisors after and before receiving Gada Madya training. The research method used was a pre-experimental design experiment with one group pretest-posttest type and hypothesis testing was carried out using the Wilcoxon test. From the results of data analysis, the Asymp. Sig. (2-tailed) 0.000 < 0.005, which means the hypothesis is accepted so there is a difference in work role performance scores for security supervisors PT. Swabina Gatra before and after being given Gada Madya training. The implications of this research state that Gada Madya training is able to improve work role performance security supervisors in PT. Swabina Gatra.